CHARACTERIZING FOOD, DAIRY, AND BEVERAGE AVAILABILITY IN PRIMARY SCHOOL PREMISES IN NORTH MACEDONIA - COSI STUDY - Mihajlova, Katerina; Wallace, Lorraine; Stamenova, Aleksandra; Spiroski, Igor (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2024)
Introduction: Childhood obesity remains a global public health challenge. Aim: Using WHO COSI-6th round data, the aim of this study was to depict availability of select foods, dairy and beverages in a nationally representative sample of primary schools across North Macedonia. Material and methods: Data were drawn from the WHO COSI-6th round conducted in North Macedonia in 2022. A designated official (n=111) at the respective primary school reported availability of the following: (1) food (fruits, vegetables, ice cream, sweet snacks, and savory snacks), (2) dairy (milk, yogurt, and/or ayran), (3) beverages without added sugar (water, tea, and fruit juices), and (4) beverages with added sugar (non-carbonated fruit juices, carbonated drinks, hot drinks [e.g., cocoa], and flavored milk). Additionally, the designated school official reported whether their primary school had a canteen and/or shop/cafeteria where foods or beverages could be purchased. Results: Across primary schools in North Macedonia, availability of healthy options (i.e., fruits and vegetables) was lower as compared to energy-dense selections (i.e., sweet and savory snacks). Overall, 18.3% of schools offered dairy products (including milk, yogurt, and ayran). Water was the most commonly available (69.0%) beverage. No significant differences emerged in availability of food, dairy, beverages without added sugar or beverages with added sugar across primary school enrollment (small versus large). Less than one-fifth of primary schools had a canteen (17.4%) and/or shop/cafeteria (14.4%) where foods or beverages could be purchased. Conclusion: In conclusion, access to food, dairy, and beverages for primary school children in North Macedonia was limited.
Keywords: primary schools; children; childhood obesity; nutrition environment; school food environment